2012
DOI: 10.1107/s1600536812035453
|View full text |Cite
|
Sign up to set email alerts
|

2-{[2,2-Bis(diethylamino)ethan-2-yliumthioyl]sulfanyl}-1,1-bis(diethylamino)ethylium bis(perchlorate)

Abstract: The title salt, C20H42N4S2 2+·2ClO4 −, was obtained from the reaction of bis­(diethyl­amino)­carbeniumdithio­carboxyl­ate, (Et2N)2C2S2, with Fe(ClO4)2·6H2O in CH2Cl2. The title compound, in which one of the S atoms of (Et2N)2C2S2 is bound to a 1,1-bis­(diethyl­amino)­ethane moiety, has two carbenium C atoms, and the charge compensation is provided by two perchlorate anions. The N2C—CS2 bond length is 1.512 (4) Å, corresponding to a C—C single bond, and the dihedral angle between N2C– and –CS2 planes [72.0 (2)°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The originalg reen solutiong radually turned brown,a nd brown crystals grew upon the addition of hexane. An X-ray crystallographic study of someofthe crystalsrevealed that two of the three EtLs were oxidized to give ad ithioperoxicarboxylate (EtLO), which formed ac ationic iron(II) complex [Fe II (EtL)(EtLO-O,S) 2 ](PF 6 ) 2 (2)i np lace of 1 ( Figure S4, Ta bles S6 [18] Synthesis of the iron(III) complex in the d 5 electronic structure was unsuccessful. For example, stirring am ixture of iron sources (e.g.,F eCl 2 ,F eCl 3 ,F e(ClO 4 ) 3 )a nd EtL in solvents (e.g., CH 2 Cl 2 ,C H 3 CN) under an Ar or air atmosphere resulted in the generation of ac omplex material( solvated iron specieso ro xidized species).…”
Section: Discussion Fe II Complex With Etlmentioning
confidence: 99%
See 1 more Smart Citation
“…The originalg reen solutiong radually turned brown,a nd brown crystals grew upon the addition of hexane. An X-ray crystallographic study of someofthe crystalsrevealed that two of the three EtLs were oxidized to give ad ithioperoxicarboxylate (EtLO), which formed ac ationic iron(II) complex [Fe II (EtL)(EtLO-O,S) 2 ](PF 6 ) 2 (2)i np lace of 1 ( Figure S4, Ta bles S6 [18] Synthesis of the iron(III) complex in the d 5 electronic structure was unsuccessful. For example, stirring am ixture of iron sources (e.g.,F eCl 2 ,F eCl 3 ,F e(ClO 4 ) 3 )a nd EtL in solvents (e.g., CH 2 Cl 2 ,C H 3 CN) under an Ar or air atmosphere resulted in the generation of ac omplex material( solvated iron specieso ro xidized species).…”
Section: Discussion Fe II Complex With Etlmentioning
confidence: 99%
“…An X‐ray crystallographic study of some of the crystals revealed that two of the three EtLs were oxidized to give a dithioperoxicarboxylate (EtLO), which formed a cationic iron(II) complex [Fe II (EtL)(EtLO‐ O,S ) 2 ](PF 6 ) 2 ( 2 ) in place of 1 (Figure S4, Tables S6 and S7 in the Supporting Information). In addition, the perchlorate analogue of 1 , [Fe II (EtL) 3 ](ClO 4 ) 2 , degraded in Et 2 O over several months at ambient temperature to give an oxidized EtL of unique dimeric structure …”
Section: Discussionmentioning
confidence: 99%
“…The two-electron-reduced species were actually isolated in the solid state, and the structures were determined by X-ray analysis . On the other hand, in the oxidation process, the RL dimerizes to give the disulfide intermediate, through which a one-sulfur-eliminated species was finally obtained …”
Section: Resultsmentioning
confidence: 99%